2016
DOI: 10.1038/srep34206
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study suggests common variants within RP11-634B7.4 gene influencing severe pre-treatment pain in head and neck cancer patients

Abstract: Pain is often one of the first signs of squamous cell carcinoma of the head and neck (HNSCC). Pain at diagnosis is an important prognostic marker for the development of chronic pain, and importantly, for the overall survival time. To identify variants influencing severe pre-treatment pain in 1,368 patients newly diagnosed with HNSCC, we conducted a genome-wide association study based on 730,525 tagging SNPs. The patients were all previously untreated for cancer. About 15% of the patients had severe pre-treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This study included patients with newly diagnosed and histologically confirmed HNSCC. The details of patient recruitment (including inclusion and exclusion criteria), the demographic characteristics and clinical data collection have been described in our previous study 34 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study included patients with newly diagnosed and histologically confirmed HNSCC. The details of patient recruitment (including inclusion and exclusion criteria), the demographic characteristics and clinical data collection have been described in our previous study 34 .…”
Section: Methodsmentioning
confidence: 99%
“…These procedures were previously described 34 . In brief, genomic DNA was genotyped using Illumina HumanOmniExpress-12v1 BeadChip (Illumina, San Diego, CA) 35 .…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the greatest known risk factor for atherosclerosis mapped by GWAS to 9p21.3 was attributed to the lncRNA ANRIL, believed to function by regulating multiple genes in trans [180,181]. Single nucleotide polymorphisms in the antisense lncRNA RP11-634B7.4 have been associated with severity of pre-treatment pain in head and neck cancer patients [182]. Furthermore, through extensive analysis of expression profiles of human lncRNAs, the FANTOM consortium found that 1970 lncRNA genes associate with at least one GWAS trait [183].…”
Section: Subtle Effectsmentioning
confidence: 99%
“…In 2016, Reyes-Gibby et al reported another genome-wide significant SNP, rs3862188 in RP11-634B7.4 gene for severe pre-treatment pain in head and neck cancer patients ( N = 1368; p = 3 × 10 −8 ) [39]. Reyes-Gibby et al identified 2 years later additional four SNPs which had statistically significant associations with neuropathic pain in head and neck cancer patients ( N = 1043; rs10950641, p = 3 × 10 −14 ; rs4804217, p = 3 × 10 −9 ; rs6796803, p = 6 × 10 −9 ; rs4775319, p = 1 × 10 −8 ) [40].…”
Section: Discussionmentioning
confidence: 99%
“…We also found three additional olfactory receptor genes ( OR52N1, OR4C12, OR4A47 ) included in the top 30 genes. Recently, Reyes-Gibby et al have reported that genetic variants in RP11-634B7.4 gene, which is annotated as antisense to the three olfactory receptor genes, OR13G1, OR6F1 , and OR14A2 , were significantly associated with severe pre-treatment pain among patients with head and neck cancer at genome-wide significance levels [39]. The olfactory receptors are members of G-protein-coupled receptors, which are involved in signal transduction and play important roles in many physiological processes including sensory perception, regulation of behavior and mood, regulation of immune system activity and inflammation, and tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%